'I don't want to hurt him.' Parents' experiences of learning to administer clotting factor to their child. (8th October 2012) - Furmedge, J.; Lima, S.; Monagle, P.; Barnes, C.; Newall, F.
Summary To explore the experiences and educational needs of parents learning to use an Implanted Central Venous Access Device (IVAD) to administer clotting factor to their child with haemophilia. Parents of children with haemophilia who had learnt to administer clotting factor via IVAD attended focus groups to discuss their experiences of the learning process. Data were transcribed and analyzed thematically. Parents described distress and trauma in dealing with the diagnosis and treatment of their child's haemophilia. It was within this context that parents began the IVAD education process. Four major themes emerged from the data: dealing with fear and anxiety; a supportive learning environment; establishing a ritual and empowerment and liberation. Parents identified a supportive learning environment as their critical need rather than a specific learning process. In addition, the concept of ritual emerged both as a mechanism for increasing the child's comfort with the procedure and as a valuable learning tool for their parents. This study highlights the importance of consulting consumers to understand their experience of illness and their educational needs. Patient and family education programs should not be limited to the provision of information, but must establish and incorporate the needs of the learner.